Influence of Paternalistic Leadership Style on Management Innovation With Demography as a Moderation Variable - Near Anggreini Hesti Noviana (Jambura Science of Management, 2022)
This study aims to see how the implementation of paternalistic leadership style influences the factors Demographics as moderator. This research takes place in two Islamic banks, namely BRI and Mandiri, which are still within the scope of the former Madiun district, namely Ponorogo, Madiun, and Magetan with a total of 104 employees as respondents. The data were processed and analyzed using the technique Moderated Regression Analysis (MRA). The results showed that the paternalistic leadership style had a positive effect on management innovation. In addition, this study proves that demographics play a moderating role in strengthening the influence of paternalistic leadership on management innovation. In this study, it was also found that the demographic factor that played a major role in moderating the influence of paternalistic leadership on management innovation was the level of education.